Sequential optimization of highly efficient all inorganic CsGeI3 perovskite solar cell by numerical simulation. (1st June 2022) - Bin Rafiq, Khan Sobayel; Mottakin, M.; Muhammad, Ghulam; Techato, Kuaanan; Sopian, Kamaruzzaman; Akhtaruzzaman, Md.
Abstract: This study models and optimizes the CsGeI3 -based perovskite solar cell with an n-i-p for practical fabrication. This simulation determined that power conversion efficiency (PCE) has practically saturated over 700 nm of thickness, and the increase rate is barely 0.15 percent up to 1100 nm. a thickness of 700 nm as the ideal thickness for further investigation. Proposed structure exhibits lower activation energy of 1.40 eV and higher thermal stability compared to others. Defect tolerance limits are found for the interfaces are 1 × 10 15 cm − 3 and 1 × 10 16 cm − 3, respectively. At visible light wavelengths of 400–800 nm, the quantum efficiency is quite high. At the hole transport layer/metal junction, the built-in potential ( V bi ) was determined in the range between 0.81 and 0.96 V. When fluorine-doped tin oxide is utilized as the front electrode and gold as the back electrode, the device's performance is at its best.